2018
DOI: 10.4149/av_2018_412
|View full text |Cite
|
Sign up to set email alerts
|

MAP9 single nucleotide polymorphism rs1058992 is a risk of EBV-associated gastric carcinoma in Chinese population

Abstract: Microtubule-associated protein 9 (MAP9) is a mitosis-associated protein involved in bipolar spindle assembly. Following DNA damage, MAP9 stabilizes p53 via p300 and MDM2 (mouse double minute-2 homolog). The dysregulation of MAP9 was considered to be associated with tumorigenesis. Single nucleotide polymorphisms (SNPs) in key genes governing mitosis may particularly increase susceptibility to gastric carcinoma (GC). Our study demonstrated that the CC homozygous genotype of SNP rs1058992 located in the MAP9 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Finally, MAP9 has been posited as a target for cancer treatment given its localization to the mitotic spindle (Liu et al, 2018;Wang et al, 2020;Zhang et al, 2022); however, we have shown that MAP9/MAPH-9 has an important role in cilia in supporting MTDs and modulating motors. Further work understanding MAP9/MAPH-9 will give insight into how MTDs are formed as well as be a protein of interest in understanding ciliopathies.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, MAP9 has been posited as a target for cancer treatment given its localization to the mitotic spindle (Liu et al, 2018;Wang et al, 2020;Zhang et al, 2022); however, we have shown that MAP9/MAPH-9 has an important role in cilia in supporting MTDs and modulating motors. Further work understanding MAP9/MAPH-9 will give insight into how MTDs are formed as well as be a protein of interest in understanding ciliopathies.…”
Section: Discussionmentioning
confidence: 86%
“…This protein can directly interact with MTs via the C-terminal domain and depletion of MAP9 leads to delay of mitotic progression and failure of cytokinesis. Thus, associations between MAP9 dysfunction and the development of tumor cells has been reported in several types of carcinomas (Liu et al, 2018;Wang et al, 2020;Zhang et al, 2020). There are also several evidences that implicate MAP9 in the formation and function of primary cilia; specific expression of the C. elegans MAP9 ortholog MAPH-9 in ciliated sensory neurons (Jensen et al, 2016;Magescas et al, 2021); map9 depletion inducing developmental abnormalities related to cilia-dependent signaling pathways in zebrafish (Fontenille et al, 2014); and localization of MAP9 in the photoreceptor CC region of canine retina (Das et al, 2017).…”
Section: Introductionmentioning
confidence: 97%